2011
DOI: 10.1190/1.3548506
|View full text |Cite
|
Sign up to set email alerts
|

Creating finite-difference time-domain models of commercial ground-penetrating radar antennas using Taguchi’s optimization method

Abstract: Very few researchers have developed numerical models of Ground-Penetrating Radar (GPR) that include realistic descriptions of both the antennas and the subsurface. This is essential to be able to accurately predict responses from near-surface, near-field targets. This paper presents detailed three-dimensional (3D) Finite-Difference Time-Domain (FDTD) models of two commercial GPR antennas-a Geophysical Survey Systems, Inc. (GSSI) 1.5 GHz antenna and a MALÅ Geoscience 1.2 GHz antenna-developed using simple analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 36 publications
(40 reference statements)
0
88
0
1
Order By: Relevance
“…The antenna models include all of the main features and geometry of the real antennas. Details of the development of antenna models and initial validation can be found in [13]. Fig.…”
Section: Antenna Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antenna models include all of the main features and geometry of the real antennas. Details of the development of antenna models and initial validation can be found in [13]. Fig.…”
Section: Antenna Modelsmentioning
confidence: 99%
“…The permittivity and conductivity of the emulsions were set by controlling ratios of the constituent chemicals [13]. A further advantage of using liquids was the ease with which targets could be positioned.…”
Section: Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into related work revealed the most common method for concrete analogs for use with GPR testing are oil-water based emulsions [9] [10] [11]. A different approach was chosen by instead developing and utilizing a sand based mixture.…”
Section: A Concrete Analogmentioning
confidence: 99%
“…To adjust the permittivity value of the material, using the approach similar utilized by [9] and [11], water was added until the desired permittivity value was obtained. To adjust conductivity values, salt (sodium chloride) could be added to raise the conductivity to suit.…”
Section: A Concrete Analogmentioning
confidence: 99%